Smallpox vaccination in 19th century Manila - de Viana, Lorelei D.C (2011)
This paper dwells on the Spanish colonial government?s efforts to introduce and implement smallpox vaccinations in 19th century Manila as part of its program to promote public health. Vaccinations were specifically carried out as a preventive measure against the dreaded scourge of olden times, smallpox or viruela, which ravaged and decimated populations not only in the Philippines, but also in other Spanish colonies. In fact, smallpox was a global scourge until the medical breakthrough of vaccination emerged. This paper studies the health efforts made by the colonial government prior to and after the introduction of vaccination in 1805, the creation of a public health bureaucracy, the establishment of sick and convalescence houses are the factors which contributed to the effectivity or ineffectivity of the vaccine program in 19th century Manila.